Pengaruh Suplementasi Minyak Ikan Lemuru Terhadap Status Kesehatan Ayam Petelur yang Diimunisasi Berulang - Ronald Tarigan; Aryani Sismin Satyaningtijas; Arif Darmawan; Dewi Prabuwati; Mutia Rahmah; Thol’at Hamdi (Jurnal Ilmu Pertanian Indonesia, 2016)
The experiment was carried out to observe the effect of adding lemuru fish oil in immunized laying hens diet on the health status of chicken through leucocyte profile, stress index, erythrocyte profile, and malonildehyde concentration in liver and spleen. The research design was completely randomized and the obtained data was analized with analysis of variance and continued with Tukey’s Post Hoc test for differences. The experiment used thirty 18 weeks hens ISA brown strain and were divided into five groups. The groups were: A (immunization with lipase and control diet); B (immunization with lipase, control diet + 1% lemuru fish oil); C (immunization with lipase, control diet + 2% lemuru fish oil); D (immunization with lipase, control diet + 3% lemuru fish oil); and E (unimmunized and control diet). The immunization was repeated three times with four weeks interval, blood was collected and analyzed two weeks after immunization and the malonyldehyde concentration in liver and spleen was measured two weeks after third immunization. The results showed that there was no significant difference (P>0.05) on all variables. The conclusion of this research that lemuru fish oil supplementation did not affect the health status of immunized hens